2009
DOI: 10.1073/pnas.0805846106
|View full text |Cite
|
Sign up to set email alerts
|

The CD5 ectodomain interacts with conserved fungal cell wall components and protects from zymosan-induced septic shock-like syndrome

Abstract: The CD5 lymphocyte surface receptor is a group B member of the ancient and highly conserved scavenger receptor cysteine-rich superfamily. CD5 is expressed on mature T and B1a cells, where it is known to modulate lymphocyte activation and/or differentiation processes. Recently, the interaction of a few group B SRCR members (CD6, Sp␣, and DMBT1) with conserved microbial structures has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 47 publications
1
95
0
Order By: Relevance
“…Consistent with this notion, rshCD5 containing all three SRCR domains aggregated FITC-labeled fungal cells (1). Two additional sets of experiments confirmed that zymosan induces CD5-dependent intracellular signaling cascades.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with this notion, rshCD5 containing all three SRCR domains aggregated FITC-labeled fungal cells (1). Two additional sets of experiments confirmed that zymosan induces CD5-dependent intracellular signaling cascades.…”
supporting
confidence: 69%
“…In this issue of PNAS, Vera et al (1) show that a naturally occurring soluble isoform of CD5 (rshCD5) binds to Schizosaccharomyces pombe, Candida albicans, and Cryptococcus neoformans fungal cells with an affinity estimated in the low nM range. The rshCD5 also bound to zymosan and binding was competed by ␤-1,3-glucan but not mannan or the bacterial carbohydrate-containing moieties PGN, LPS, or LTA.…”
mentioning
confidence: 99%
“…In some instances, the amino acid sequence motifs involved in SRCR-mediated pathogen recognition have been precisely identified (RxR, VEVLxxxxW) (15,16,20), but an exact match to these motifs is not observed among any of the SRCR domains of S5D-SRCRB. However, by no means does this exclude the SRCR domains of mouse S5D-SRCRB as being responsible for pathogen recognition, as exemplified by Spa, CD6, and CD5 (17)(18)(19). The SRCR domains are among the few protein modules from which evolution has settled a myriad of structurally related but functionally different proteins.…”
Section: Discussionmentioning
confidence: 99%
“…They do not possess enzymatic activity; however, some SRCR domains have been involved in protein-protein interactions, the best studied examples being those of CD6 with CD166/ALCAM (4) and CD163 with the haptoglobin-hemoglobin complex (14). In recent years, a number of studies also supported the recognition of PAMPs by some, but not all, group A (i.e., MARCO) (15) and B (i.e., DMBT1/SAG/gp340, Spa, CD6, CD5, and CD163) (16)(17)(18)(19)(20) SRCR-SF members. Group B is composed of about a dozen members expressed in mammals by immune cells, such as macrophages (i.e., CD163/M130, CD163L1/M160, Spa/AIM) or lymphocytes (i.e., CD5, CD6, SCART, WC1), as well as by cells of the gastrointestinal, respiratory, and genitourinary tracts (i.e., DMBT1/ SAG/gp340, S4D-SRCRB, 18-B) (5,21).…”
mentioning
confidence: 99%
“…In addition to dectin-1 and CR3, other receptors have been reported to bind β-glucans, including lactosylceramide, scavenger receptors, and CD5. 84,85 GPs are also potent activators of the alternative complement pathway, which leads to deposition of opsonic C3 fragments on the surface of GPs. GPs stimulate DCs to produce cytokines such as IFN-γ and IL-17, which are associated with beneficial responses in vaccine models of pathogen protection.…”
mentioning
confidence: 99%